Resilience of the Bucharest Nine Countries in the Context of Global Turbulence - Lebedeva, Larysa; Shkuropadska, Diana; Gonçalves , Jorge; Shtunder, Iryna; Ozhelevskaya, Tatyana; Yasko, Yuliya (International Journal of Economics and Financial Issues, 2025)
Ensuring the resilience of the Bucharest Nine (B9) countries is crucial for regional and Euro-Atlantic security, with the challenges such as Russia’s aggression against Ukraine, hybrid warfare threats, regional tensions, etc. The goal of this research is to assess the resilience levels of the B9 countries and to identify aspects of their vulnerabilities and capacities to withstand global turbulence. This study analyses the Resilience Dashboards by the European Commission. The findings indicate that most B9 countries have a medium level of vulnerability, aligning with the EU27 average, while their capacity levels remain below the EU27 average. The analysis highlights that B9 countries demonstrate medium socio-economic resilience, with improvements in employment but persistent challenges in health and education with Czechia being the most resilient in this category. In green resilience, Estonia, Czechia, and Poland perform best, though still below the EU27 average, while Bulgaria and Romania face significant environmental challenges. Digital resilience shows notable positive shifts, with improvements in cybersecurity and digital skills, but challenges persist in broadband access and online public services. Estonia leads in digital resilience, while Bulgaria and Romania lag. Geopolitical resilience is at medium level. Hungary, Estonia, Lithuania, and Latvia have the highest geopolitical capacities, whereas Romania remains the most vulnerable.